Islamic astronomical tables - Dalen, Benno van, author.
1 online resource
Keywords: This volume comprises nine articles on Islamic astronomy published since 1989 by Benno van Dalen. Van Dalen was the first historian of Islamic astronomy who made full use of the new possibilities of computers in the early 1990s. He implemented various statistical and numerical methods that can be used to determine the mathematical properties of medieval astronomical tables, and utilized these to obtain entirely new, until then unattainable historical results concerning the interdependence of individual tables and hence of entire astronomical works. His programmes for analysing tables, making sexagesimal calculations and converting calendar dates continue to be widely used. The five articles in the first part of this collection explain the principles of a range of statistical methods for determining unknown parameter values underlying astronomical tables and present extensive step-by-step examples for their use. The four articles in the second part provide extensive studies of materials in unpublished primary sources on Islamic astronomy that heavily depend on these methods. The volume is completed with a detailed index.